2006
DOI: 10.1136/jcp.2004.024687
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of stage IV neuroblastoma metastatic immunophenotype in the bone marrow: preliminary report: Table 1

Abstract: Aim: To correlate the immunophenotype of metastatic cells in the bone marrow of patients with neuroblastoma with early treatment failure. Methods: The studies were performed on bone marrow material obtained from children treated in the department of paediatric oncology, haematology, and transplantology, Poznan University of Medical Sciences, Poland from 1996 to 2003. Immunocytochemical analysis of nervous tissue markers (using the immunomax technique) was performed on 108 bone marrow preparations obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
(10 reference statements)
5
11
0
Order By: Relevance
“…In line with this, blocking Y5R inhibited neuroblastoma xenograft growth via an increase in apoptosis and sensitized resistant neuroblastoma cells to chemotherapy (Czarnecka et al, 2015). This data supports previous clinical observations indicating associations of high NPY levels in neuroblasts infiltrating bone marrow, as well as a lack of normalization of systemic NPY after treatment with rapid neuroblastoma relapse and its fatal outcome (Dotsch et al, 1998; Nowicki et al, 2006; Rascher et al, 1993). As neuroblastoma cells originate from precursors of sympathetic neurons, the pro-survival effect of NPY in these cells is in line with its known neuroprotective activity in various types of normal neurons that are known to be mediated by the p44/42 MAPK pathway (Decressac et al, 2012; Malva et al, 2012).…”
Section: Tumor Cell Survival and Chemoresistancesupporting
confidence: 92%
“…In line with this, blocking Y5R inhibited neuroblastoma xenograft growth via an increase in apoptosis and sensitized resistant neuroblastoma cells to chemotherapy (Czarnecka et al, 2015). This data supports previous clinical observations indicating associations of high NPY levels in neuroblasts infiltrating bone marrow, as well as a lack of normalization of systemic NPY after treatment with rapid neuroblastoma relapse and its fatal outcome (Dotsch et al, 1998; Nowicki et al, 2006; Rascher et al, 1993). As neuroblastoma cells originate from precursors of sympathetic neurons, the pro-survival effect of NPY in these cells is in line with its known neuroprotective activity in various types of normal neurons that are known to be mediated by the p44/42 MAPK pathway (Decressac et al, 2012; Malva et al, 2012).…”
Section: Tumor Cell Survival and Chemoresistancesupporting
confidence: 92%
“…For example, starting from the knowledge that metastatic neuroblastoma cells in bone marrow have a different immunophenotype than that found in cells of the primary focus [87], a study conducted on 36 children (aged 4-18 years) with stage IV neuroblastoma and with bone marrow metastases showed that in metastatic cells there was a significant correlation between early recurrence of the disease and NPY expression evaluated by immunoistochemical staining [88]. Hence, in patients with stage IV neuroblastoma, NPY could be a strong marker of an unfavourable prognosis.…”
Section: Npy and Receptors As A Tumoral Bio-markersmentioning
confidence: 99%
“…Unfavourable prognostic factors involve the age >1 yr, stadia 3 and 4 (except of 4S), high mitotic rate [15], diploidy, N-myc amplification [16][17][18], partial gain of the distal long arm of chromosome 17 [16], deletion of the distal short arm of chromosome 1 [19], high expression of telomerase and certain neuropeptide markers expression [20][21][22][23]. Similarly, the vessel density in NB correlates with tumour stage and outcome [24].…”
Section: Introductionmentioning
confidence: 99%